ANALISIS VEGETASI PADA TIPE-TIPE HUTAN DALAM KAWASAN CAGAR ALAM PANGI BINANGGA KABUPATEN PARIGI MOUTONG - Pongmasamban, Hendric; Sudhartono, Arief; Irmasari, Irmasari (Jurnal Warta Rimba, 2015)
The main function of Pangi Binangga Nature Reserve is as an area for protection of ebony (Diospyros celebica Bakh) species. The aims of this study was to analyze vegetation based on forest types in Pangi Binangga Nature reserve area. Study was conducted from March through May 2013. This research was use transect methods by purposive sampling. Classification of the forest based on the altitudes, i.e; 469 m asl (lowland forest) and 830 m asl (highland forest). The results showed that the vegetation at lowland forest (469 m asl) was dominated by Dracotamelon dao with important value index (IVI) (34.15%), and it was followed by Lithocarpus sp (36.26%), Palaqium obovatum (42.04%) and Asplenium nidus L (24.17%), at the tree, pole, sapling and seadling levels, respectively. Furthermore, the vegetation at highland forest (839 m asl) was dominated by Pometiapinnata J.R Forst with important value index (IVI) (42.25%), and it was followed by Conanga ordorata (57.12%), Michelia champaca (43.48%), and Memordica cochinchinensis (29.39%), at the tree, pole, sapling and seadling levels, respectively. Hence, index of similarity and index of dissimilarity between both forest types was 30.55%. Its means that similarity of the vegetation in this location was less (â‰¤ 50%). Keyword: Vegetation analysis, Forest types, Altitude, Important Value Index.